Study on Shale’s Dynamic Damage Constitutive Model Based on Statistical Distribution - Jianjun Liu; Yuan Li; Huijuan Zhang (Shock and Vibration)
The dynamic constitutive model of shale is basic for shale gas reservoir reforming. In order to investigate the dynamic mechanism of shale, a new dynamic damage constitutive model of shale under uniaxial impact load was established based on the statistical damage theory and the laboratory test results of deformation and the damage characteristics under the action of SHPB impact. Compared with the theoretical results, the model can describe shale’s mechanical attributes and reveal the fracture damage mechanism as well. The results will provide theoretical basis for hydraulic fracturing on shale and other dynamic reforming technics.